Transliterasi, Serapan, dan Padanan Kata: Upaya Pemutakhiran Istilah dalam Bahasa Indonesia - Hudaa, Syihaabul (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2019)
Indonesian has a word formation variant as an effort to update the vocabulary. However, not many people who use language know the terms transliteration, absorption and equivalent words in Indonesian. This makes a word accepted without knowing the original word form. The purpose of writing this article is to describe vocabulary written in the form of transliteration, absorption, and also equivalent words in Indonesian. The methodology used in this study is content analysis by focusing on the text used as the object of study. The results of research findings conducted by researchers are the existence of vocabulary in the form of transliteration, absorption, and equivalents that are often used in communication. The researcher gives an explanation of a word that is included in transliteration, absorption, and equivalence.Keyword: word form; language update; language terms.